The Factors Affecting Nursing Students’ Career Choices in Turkey: A Cross-sectional Study - Burçin Selçuk; Hatice Serap Koçak; Zeynep Güngörmüş (علوم بهداشتی ایران)
Background and Purpose: Career choice, one of life’s most important decisions, can affect the future income level and related lifestyle and life quality. This study aims to determine the factors affecting the career choice among Turkish nursing students. Materials and Methods: This is a cross-sectional study. The participants were 2778 nursing students of state universities from seven geographical regions of Turkey who were selected by drawing lots. A sociodemographic form and the vocational choices in entering nursing scale (VCENS) were used to collect the data. Mann-Whitney U test, ANOVA, Kruskal-Wallis test, and analysis of variance were used to analyze the data. Results: The mean total score of the VCENS was high (101.41±24.89). Regarding its subscales, the mean score of the congruence subscale (70.51±20.83) was higher than the mean score of the survival subscale (30.9±10.24). There were significant differences in the total score and subscales scores of the VCENS based on students’ age, gender, the study university, educational year, and family income status (P<0.05). Based on the reports, 65.2% of students voluntarily chose the department of nursing, 43.2% perceived the theoretical education as sufficient, and 35.4% perceived the practical/clinical education as inadequate. Conclusion: The career choices of nursing students in Turkey differ according to the region. The high mean score of students in the congruence subscale indicates that they make a conscious choice. Most of them perceive that the practical/clinical education provided by universities is inadequate. Arranging classroom sizes by increasing the number of lecturers and screening their performance can help improve the current situation.